The Influence of Environmental Knowledge and Perceived Value on Sustainable Fashion Purchase Intention: The Mediating Role of Attitude - Marsa Septiarni; Nur Afifah; Ana Fitriana; Haryadi; Ahmadi (Al-Qalam Institue, 2026)
The rapid growth of fast fashion, which increasingly contributes to environmental degradation, has encouraged greater awareness of sustainable fashion consumption. This study aims to analyze the influence of environmental knowledge and perceived value on sustainable fashion purchase intention, with attitude serving as a mediating variable. Employing a causal associative quantitative approach, primary data were collected through an online questionnaire distributed to 200 respondents who met predetermined criteria using non-probability purposive sampling. The measurement used a five-point Likert scale, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings indicate that environmental knowledge and perceived value have a positive and significant effect on attitude, which in turn significantly mediates their influence on sustainable fashion purchase intention. These results imply that enhancing consumers’ environmental understanding and strengthening perceived value are essential strategies for fostering positive attitudes and increasing purchase intentions toward sustainable fashion products.